L’intervento precoce nelle psicosi: un cambio di paradigma - Bensi, Marco; Armando, Marco; Righetti, Valentino; Saba, Riccardo; Monducci, Elena; Fiori Nastro, Paolo (Il sogno della farfalla, 2010)
The attention of psychiatrists and researchers is shifting ever more from the management of chronicity towards the early phases of the development of mental illness, in particular within the ambit of psychoses. Therefore, there are many early intervention protocols in operation at an international level, that are currently based on a set of prevention, diagnostic and therapeutic measures, inherent to the prodromic state as well as the first psychotic episode. This article offers a broad overview of the information and sensibilization campaigns on psychiatric themes, on the strategies and identification instruments of the “mental states at risk”, and on the more innovative characteristics of the modern services dedicated to the onset of psychosis. If, on the one hand, the importance of these elements in the perspective of an improved course and prognosis of an illness is highlighted, on the other hand we must be warned of the risk that what we consider a changing paradigm in psychiatry, in getting away from “encephalopathy”, may transform itself into “sociopathy”. In other words, what the authors agree on, from a pragmatic point of view, can lose meaning totally if there is not an underlying valid theoretical structure on human beings.